Managing multimorbidity: a qualitative study of the Australian general practitioner experience. (5th September 2022) - Damarell, Raechel A; Morgan, Deidre D; Tieman, Jennifer J; Senior, Tim
Abstract: Background: Multimorbidity is prevalent in general practice and general practitioners internationally report challenges in its management. Understanding the perspectives of general practitioners at the frontline of care is important for system sustainability and accessibility as populations age. Objective: To explore Australian general practitioner perspectives on managing multimorbidity, the factors supporting their work, and those impeding their ability to meet their own standards of care provision. Method: A qualitative study conducted with Australian general practitioners using semistructured, in-depth interviews and inductive thematic data analysis. Results: Twelve interviews with general practitioners were conducted. Three main themes were constructed from the data: Multimorbidity as an encounter with complexity and contingency; Evidence constraints in multimorbidity care; and Concerns for patient safety. System structure and the Australian general practice model restrict general practitioners' ability to provide care to their level of satisfaction by linking short consultation times to practice remuneration. Attitudes toward the applicability of guideline evidence were mixed despite most general practitioners questioning its generalizability. Patient safety concerns pervaded most interviews and largely centered on system fragmentation and insufficient intersectoral communication. General practitioners rely on multiple sources of information to provide patient-centered care but chiefly the accumulated knowledge of their patients. Conclusions: Australian general practitioners share many multimorbidity concerns with international colleagues. While multimorbidity-specific evidence may be unrealistic to expect in the immediate term, system investment and adaptation is needed to support general practice sustainability and clinician ability to provide adequate multimorbidity care, suitably remunerated, into the future.